Caracterização de efeitos dispersivos em dados de GPR causados por bandas de deformação em arenitos: petrofísica, modelagem numérica e análise multiatributo - Cedraz, Victória Maria de Almeida Santos (2024)
We evaluate the dispersive effect on Ground-Penetrating Radar (GPR) data caused by deformation bands (DBs) present in sandstones. To achieve this objective, we used a 200 MHz GPR cube surveyed on a sandstone outcrop, highly impacted by DBs, located in the Rio do Peixe Basin (Northeast Brazil). To interpret the GPR cube, we developed an integrated and multidisciplinary approach that consisted of two stages. The first stage was based on laboratory measurements and numerical modeling and the second stage was based on multi-attribute analysis. In the first stage, complex dielectric constant measurements of clean sandstones (50-400 MHz frequency range) revealed that the quality factor (Q) is strongly influenced by grain size: Q decreases as grain size decreases. Therefore, DBs are associated with relatively low Q values because they always cause grain reduction compared to the host rock. Furthermore, two-dimensional modeling of radargrams confirmed the empirically known fact that DBs appear as zones of attenuated signal in two case studies: a conceptual model of DBs and the approximate reproduction of one of the GPR cube sections. The second stage consisted of extracting the threedimensional architecture of the DBs from the GPR cube using a multi-attribute analysis. We showed that the sequential application of the edge evidence and ant-tracking attributes was able to automatically identify continuous zones of attenuated signal within the GPR cube. As a result, it was possible to extract the DBs as a geobody. The geological reliability and limitations of the geobody were evidenced by comparing sections of it with photographs of DBs exposed in similar positioning, in addition to structural measurements obtained in the field and in the geobody.